Accelerating Business Processes through Digitalization Efficiency: The Roles of Digitalization, Strategic Alignment, and Organizational Readiness - Citra Fithri Annisa; Ependi Ependi; Agus Rizal (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Digital transformation has become a strategic priority for organizations seeking to enhance operational efficiency and accelerate business processes in an increasingly competitive environment. However, the effectiveness of digital transformation initiatives is influenced by various organizational and technological factors. This study aims to examine the effects of Digitalization Factors, Strategic Alignment, and Organizational Readiness on Digitalization Efficiency and Process Speed at PT XYZ, with Digitalization Efficiency serving as an intervening variable. A quantitative research approach was employed using a survey questionnaire distributed to employees involved in digitalization processes. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings indicate that Digitalization Factors (β = 0.418; p < 0.001) and Strategic Alignment (β = 0.435; p < 0.001) have positive and significant effects on Digitalization Efficiency, whereas Organizational Readiness does not significantly influence Digitalization Efficiency (β = 0.071; p = 0.484). Regarding Process Speed, Strategic Alignment has a positive and significant effect (β = 0.321; p = 0.001), while Organizational Readiness exhibits a significant negative effect (β = -0.223; p = 0.002). Digitalization Efficiency significantly mediates the effects of Digitalization Factors and Strategic Alignment on Process Speed but does not mediate the effect of Organizational Readiness. The model demonstrates strong predictive capability, with R² values of 0.688 for Digitalization Efficiency and 0.837 for Process Speed. These findings highlight the critical role of strategic alignment and digitalization efficiency in accelerating business processes and supporting successful digital transformation initiatives.